Multigene profiling of single circulating tumor cells - Park, Seung-min (Mol Cell Oncol, 2017)
Numerous techniques for isolating circulating tumor cells (CTCs) have been developed. Concurrently, single-cell techniques that can reveal molecular components of CTCs have become widely available. We discuss how the combination of isolation and multigene profiling of single CTCs in our platform can facilitate eventual translation to the clinic.